THE CONFIGURATIONS OF THE PROCESS OF DOING, FEELING, THINKING, AND RELATING IN LAMPUNGESE LANGUAGE CLAUSES - Afrianto Afrianto; Eva Tuckyta Sari Sujatna; Nani Darmayanti; Farida Ariyani (Leksema: Jurnal Bahasa dan Sastra, 2024)
This descriptive-qualitative research explores the processes configured in Lampungese language clauses. Here, the processes are structured in clauses showing physical actions, feelings, thinking, relation, behaviour, and existence. It investigates the processes using Hallidayan transitivity system and focuses on the constituents forming a clause, such as participant, process, and circumstance. In order to keep a natural setting, the data of this research were collected by documentation from passages of six lesson books of Lampungese language. The results of analyses show that the process of doing is realized with nyeghbu, ngemulai perlawanan, ngelawan, ngebantu, ditulis and diteghusko, whereas the mental process is constituted by nyeghah, ngenal, nganggop, and dikenang. Meanwhile, the realization of relational process is dimaksudko, which is classified as an identifying relational process. It is also found that a relational clause can be structured without any relational process. The disappearance of the process can be categorized as zero relational process and marked with 0.  The result of this research is expected to give a contribution to document the structure of the Lampungese language.